Answer:
![f(x) = -4(x+7)(x+1)](https://img.qammunity.org/2022/formulas/mathematics/college/np0ziiqexn6a428r112msstuuhucs72klu.png)
Explanation:
Quadratic equation:
A quadratic equation, with roots(x-intercepts) at
and
, and leading coefficient a, is given by:
![f(x) = a(x - x_1)(x - x_2)](https://img.qammunity.org/2022/formulas/mathematics/college/9jj05xl1mkpyxacm0usvopz2zckhgctcll.png)
Has x-intercepts of -7 and -1
So
. Thus
![f(x) = a(x - (-7))(x - (-1)) = a(x+7)(x+1)](https://img.qammunity.org/2022/formulas/mathematics/college/s4fu1b092oy91tjva74948qahlkaccuq5j.png)
Passes through the point (-4,36).
This means that when
, and we use this to find the leading coefficient.
![36 = a(-4+7)(-4+1)](https://img.qammunity.org/2022/formulas/mathematics/college/3lgrdkxz9zcqm1mcoqucr2ax401twa4h77.png)
![a(3)(-3) = 36](https://img.qammunity.org/2022/formulas/mathematics/college/o3jiocmu7cjuyjj2mabplh9yqu40nfb8au.png)
![-9a = 36](https://img.qammunity.org/2022/formulas/mathematics/college/jkax1yzu75p2k1icimoh11zg01rogsom77.png)
![a = -(36)/(9)](https://img.qammunity.org/2022/formulas/mathematics/college/yt7wmx96dcuhyxlrnj9f5akve465uuya0q.png)
![a = -4](https://img.qammunity.org/2022/formulas/mathematics/college/n4ftrqd94j7ggzm0g4cp8007cbbciuxp8n.png)
So
![f(x) = -4(x+7)(x+1)](https://img.qammunity.org/2022/formulas/mathematics/college/np0ziiqexn6a428r112msstuuhucs72klu.png)